ANALISIS EFISIENSI PEMASARAN DAN MUTU GULA AREN DI KABUPATEN KUANTAN SINGINGI - Siti Muslimah; Evy Maharani; Susy Edwina (UIR Press, 2017)
Palm sugar is a product derived from palm juice water treatment are already known by the general public. Palm sugar can be used as processed food ingredients, can be used as a medicine and can be used as business venture opportunities. The purpose of this study was to analyze the level of marketing efficiency and recognize quality palm sugar according to retailers and end customers in Kuantan Singingi. The study was conducted in April-December 2016. The research method used survey method and sampling craftsmen census method as many as 11 respondents. The results showed that the marketing channel there is two palm sugar Custom-retailer-consumer end; Craftsmen palm sugar-end consumers. Value marketing efficiency on the channel I was 10.79% and the efficiency of marketing channels II is 8.80%. Palm sugar marketing more efficient channel of distribution II because the process is shorter than the first channel and marketing channel II was able to spend with low. Description of quality of palm sugar by craftsmen, retailers and end customers meets the criteria that can be seen from the National Quality Standards, namely: the color